Comparative Pharmacokinetics of Gallic Acid After Oral Administration of Gallic Acid Monohydrate in Normal and Isoproterenol-Induced Myocardial Infarcted Rats - Yu, Zhe; Song, Fan; Jin, Yu-Chen; Zhang, Wei-Min; Zhang, Ya; Liu, En-Jun; Zhou, Dan; Bi, Lin-Lin; Yang, Qian; Li, Hua; Zhang, Bang-Le; Wang, Si-Wang (Frontiers in Pharmacology, 2018)
Gallic acid (GA) is a polyphenolic natural product widely distributed in food, beverage and traditional Chinese herbs with beneficial effects on the cardiovascular system. In this research, a comparative study was conducted to investigate the possible difference of pharmacokinetic process in normal and isoproterenol-induced myocardial infarcted rats after oral administration of gallic acid monohydrate with the dose of 50 and 100 mg/kg, respectively. Quantification of GA in rat plasma was achieved by using a simple and rapid high-performance liquid chromatographic (HPLC) method. The results revealed that pharmacokinetics of GA were greatly different between normal and pathological state. GA exhibited slower absorption into the bloodstream, and yielded 1.7-fold (50 mg/kg GA) and 1.3-fold (100 mg/kg GA) less values of area under concentration–time curve (AUC) as well as 2.5-fold lower of maximum blood concentration (Cmax) in MI rats than those in normal rats. In addition, significant prolonged T1/2 and MRT as well as decreased CL were also registered in MI rats. Our findings suggest that myocardial infarction could alter the pharmacokinetic process of gallic acid, and thus the potential pharmacokinetic differences of herbal preparations (or dietary nutrition) containing GA between normal and pathological conditions should be brought to the forefront seriously in clinical practice.